Do low self-esteem, relationship dissatisfaction and relationship insecurity exacerbate the intention to break up in romantic relationships? - Arikewuyo, Abdulgaffar Olawale; Eluwole, Kayode Kolawole; Dambo, Tamar Haruna; Abdulbaqi, Saudat Salah (Springer, 2022)
This research investigated the extent to which low self-esteem, relationship dissatisfaction, and relationship insecurity exacerbate intention to break up in romantic relationships. Results from the study indicated that low self-esteem contributed to individuals having negative thoughts, emotions, and evaluation of their romantic relationships. Quite importantly, findings in the study showed that insecurity and relationship dissatisfaction partially mediate the relationship between low self-esteem and intention to break up in romantic relationships. Findings also indicated that due to low self-esteem, individuals may begin to doubt the level of trust, love and care accorded them by their romantic partners.
Keywords: Low self-esteem; Relationship dissatisfaction; Relationship insecurity; Intention to break up; Romantic relationships